1994
DOI: 10.1055/s-2007-1001761
|View full text |Cite
|
Sign up to set email alerts
|

L-Thyroxine (T4) Elevates the Free Amino Acid Pool of Haemolymph Plasma of Tasar Silkworm, Antheraea mylitta Drury (Lepidoptera: Saturniidae)

Abstract: Concentration of free amino acids (FAA) in the haemolymph plasma of male and female tasar silkworm, A. mylitta, during fifth larval instar were determined by amino acid analyzer after administration of vertebrate thyroxine (T4). Twenty FAA have been identified in haemolymph plasma in both sexes, out of which ten were found to be predominating. Treatment with anabolic doses of thyroxine (0.5 and 1.0 micrograms/g) were able to enhance the titre of all the individual FAA which has been also reflected in the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
(12 reference statements)
2
1
0
Order By: Relevance
“…Narayanan (1973) found an obvious increase in the total amino acids in the larvae of Plutella maculipennis curt treated with B. thuringinesis. Similar observation was also reported by Reddy et al (1994) in thyroxine treated fifth instar larvae of tasar silkworm, Antheraea mylitta. Pant and Agrawal (1964) suggest that all amino acids found were likely to contribute a general pool for the synthesis of new proteins and for the products of protein breakdown, osmoregulation and buffering.…”
Section: Quantitative Estimation Of Total Amino Acids and Free Amino supporting
confidence: 89%
“…Narayanan (1973) found an obvious increase in the total amino acids in the larvae of Plutella maculipennis curt treated with B. thuringinesis. Similar observation was also reported by Reddy et al (1994) in thyroxine treated fifth instar larvae of tasar silkworm, Antheraea mylitta. Pant and Agrawal (1964) suggest that all amino acids found were likely to contribute a general pool for the synthesis of new proteins and for the products of protein breakdown, osmoregulation and buffering.…”
Section: Quantitative Estimation Of Total Amino Acids and Free Amino supporting
confidence: 89%
“…Interestingly, a higher dose of T4 (3.0 µg/g) depressed the ATPase activity by 13-32%, indicating the biphasic nature of thyroid hormone action. A similar biphasic nature of T4 action was observed in the protein and nucleic acid content of fat body cells of B. mori (Chaudhuri and Medda, 1987a), amino acid titer in haemolymph of Antheraea mylitta (Reddy et al, 1994b), protein and nucleic acid turnover in gonads of A. mylitta (Reddy, et al, 1994c), and the vertebrate liver (Medda and Ray, 1979). Our earlier findings revealed that lower than a 0.5 µg/g dose of T4 remained less effective/ineffective in altering the protein, nucleic acids, and glycogen metabolism in fat body and ovarian cells of B. mori Medda, 1987a,b 1993).…”
Section: Resultssupporting
confidence: 64%
“…growth, survival, induction of metamorphosis). Some specific actions of exogenous application of T 4 during the early life histories of insects, the most studied arthropods, point to its influential effects on protein, nucleic acids, glycogen, and amino acid metabolism, ecdysteroid content and activity of membrane enzymes (Thyagaraja, Kelly, Masler & Borkovec 1991; Reddy, Chaudhuri & Sukumar 1994; Reddy, Chaudhuri & Thangavelu 1994). Thyroid hormones and their derivatives have also been suggested to act as vitamins (obtained through the food chain) in various stages of the life cycle in invertebrates, including their early life histories (Eales 1997).…”
Section: Growth Expressed As Mean Developmental Stage For Macrobrachmentioning
confidence: 99%